2020
DOI: 10.1080/10508422.2020.1776617
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and ethical decision-making

Abstract: Self-efficacy is the assessment of one's capacity to perform tasks. Previous research has demonstrated that self-efficacy impacts ethical behavior and attitudes but its effect on ethical cognition and perceptions has not been studied. For the present study, participants analyzed an ethical dilemma after either high or low self-efficacy was induced. Participants analyzed the dilemma using one of two cognitive problem-solving techniques (a structured cognitive tool or an unstructured cognitive technique) versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…This suggests that participants perceived that they were more capable of handling the ethical misconduct of others following participation in the training. Indeed, this is consistent with previous research which suggests that engaging in an ethics intervention can increase confidence in one's ability to face an ethical dilemma (Stenmark et al, 2020). Thus, participation in even a shortened, 1-day training, can have valuable effects on the confidence of individuals in how to deal with ethical problems they may face in the future.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that participants perceived that they were more capable of handling the ethical misconduct of others following participation in the training. Indeed, this is consistent with previous research which suggests that engaging in an ethics intervention can increase confidence in one's ability to face an ethical dilemma (Stenmark et al, 2020). Thus, participation in even a shortened, 1-day training, can have valuable effects on the confidence of individuals in how to deal with ethical problems they may face in the future.…”
Section: Discussionsupporting
confidence: 90%
“…They prefer to persevere in their studies rather than leave the work environment. This result is akin to some studies in the literature (e.g., Stenmark et al, 2021;Tai et al, 2012).…”
Section: Conclusion and Discussionsupporting
confidence: 85%
“…It has been observed that academics with high SE have similarities in strengths and weaknesses despite being in different fields of expertise (Hemmings et al, 2012). They can cope with difficult situations in the business environment more efficiently (Stenmark et al, 2021) and can contribute to the implicit knowledge sharing behaviors within higher education institutions (Rahman et al, 2018). Determining the SE levels of academics in the relationship between feelings of workplace envy and intention to quit will benefit the experts working in the fields of organizational behavior and human resources in the effective management of the qualified workforce.…”
Section: Introductionmentioning
confidence: 99%
“…The corporate environment is always changing, and in the virtual workspace, employees are frequently working in new environments where conventions have yet to be formed and prototypes are limited. Therefore, employees frequently count on their higher-order cognitive skills (Stenmark et al, 2020 ), and, as any skilled tradesman, they require the tricks of the trade to do so effectively (Stenmark et al, 2019 ). The more an organisation can equip employees with moral norms to apply in diverse circumstances (as well as opportunities to apply them), the more likely they will utilise them to effectively solve their issues.…”
Section: Discussionmentioning
confidence: 99%